Report on Work Package 2: "Governance Analysis". Case studies: Halle-Neustadt, Berlin-Marzahn. Research project "States after Transition" (MOBERA-14, Era.NET RUS PI). - Bernt, Matthias (My University, 2020)
The report summarizes the findings of the Work Package 2 “Governance Analysis” of the comparative research project “Estates After Transition”. This 3-year research project compares six large housing estates in three countries (Russia, Germany, and Estonia). The analysis of governance arrangements is a central part of this project. Its specificity lies in comparing political dynamics and planning decisions three very different institutional and economic environments. Against this background, the German cases (Halle-Neustadt and Marzahn) represent the marketization and privatization of a rental housing system still marked by intensive state intervention and public planning.
Erscheinungsjahr ermittelt.
Keywords: Großwohnsiedlung; Großwohnanlage; Kommunale Wohnungspolitik; Wohnungsplanung; Wohnungswirtschaft; Wohnungsmarkt; Privatisierung; Stadtumbau Ost